Population genetics of Rhizophora apiculata in peninsular malaysia using microsatellite markers / Amelia Azman - Amelia , Azman (2020)
Rampant illegal logging, overharvesting and deforestation coupled with climate change, pose significant threats to the natural stands of Rhizophora apiculata, or locally known as Bakau Minyak; one of the most economically and ecologically important species of mangroves in Peninsular Malaysia. Despite being a dominant mangrove species, the reduction in the number of R. apiculata in its habitat has resulted in concerns over the long-term survival potential of the species. In Malaysia, genetic information to develop effective guidelines for the conservation and management of mangrove species has been lacking, and hence, further research should be conducted to fill this gap. The present study was therefore designed to generate novel genetic information for R. apiculata, aiming to facilitate the efforts to maintain the genetic diversity of the species in Peninsular Malaysia. A set of novel genic microsatellite markers was generated using an in-house transcriptome dataset of R. apiculata to assess its level of diversity and population differentiation throughout Peninsular Malaysia. A total of 22 identified polymorphic markers were validated and used to genotype 1,120 individuals collected from 39 natural populations of R. apiculata, uncovering its low genetic diversity (He: 0.3523) and high population differentiation (Fst: 0.3150). Low genetic diversity may indicate the occurrence of inbreeding or low levels of gene flow. Based on the microsatellite marker analysis, the populations were separated into two major clusters, corresponding to eastern and western regions of Peninsular Malaysia and coinciding with the Straits of Malacca and the South China Sea. The genetic information generated in this study will enable the formulation of in situ and ex situ conservation guidelines for R. apiculata in Peninsular Malaysia. Additionally, the genic microsatellite markers generated from this study can be used for future research such as population genetic studies of other closely related species as well as for specific applications such as DNA profiling and forensic analysis.